Case Report: Next-Generation Sequencing in Diagnosis of Pneumonia Due to Pneumocystis jirovecii and Cytomegalovirus in a Patient With HIV Infection - Xie, Yirui; Ruan, Bing; Jin, Lingxiao; Zhu, Biao (Frontiers in Medicine, 2021)
Background: Pulmonary infections remain as a significant cause of morbidity and mortality in immunocompromised patients. The pathogens spectrum of pulmonary infection that can affect patients with human immunodeficiency virus (HIV) is wide such as bacterial, fungal, viral, parasitic organisms and so on. The risk of multipathogenic pneumonia is higher in HIV-infected patients. However, the fast and accurate diagnose of multipathogenic pneumonia is challenging because the limitations of the current conventional tests. Case presentation: Here, we report a case of pneumonia due to Pneumocystis jirovecii (P. jirovecii) and Cytomegalovirus (CMV) in a 22-year-old male with newly diagnosed HIV infection. Blood tests revealed a low CD4 count, chest computed tomography (CT) scan showed extensive ground-glass opacities in bilateral lungs with multiple cavity lesions in left upper lungs. Microscopic examination of stained sputum and bronchoalveolar lavage fluid (BALF) smear specimens did not find any pathogens. There was also no evidence for pathogens known to cause pneumonia in bacteria and fungi culture tests and virus antibody such as EBV, CMV and COVID-19. The nucleic acid of CMV in blood was reported by quantitative PCR. Next-generation sequencing (NGS) analysis of BALF specimen identified a large number of P. jirovecii and CMV reads, and allowing to confirm the diagnosis of pneumonia due to P. jirovecii and CMV. Following the patient’s treatment with anti-PCP and anti-CMV, the patient was cured and discharged. Conclusions: This case highlights the combined application of NGS in the clinical diagnosis of multipathogenic pneumonia in the HIV-infected patient. NGS is proposed as an important adjunctive diagnostic approach for identifying pathogens of multipathogenic pneumonia in the HIV-infected patients.